Pengembangan Pesantren sebagai Learning Organization Berbasis Kearifan Lokal Menuju Keberlanjutan Organisasi Pendidikan: Studi Kasus di Kalimantan Timur - Muhammad Sali; Akhmad Muadin (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2024)
This study examines how local wisdom contributes to the organizational sustainability of Islamic boarding schools (pesantren) by integrating it within a learning organization framework. While previous studies often position local wisdom as a cultural identity element, limited research explores its strategic role in strengthening institutional sustainability. This research employs a qualitative case study approach at Pesantren Trubus Iman Paser. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using an interactive model involving data reduction, data display, and conclusion drawing to ensure credibility and thematic coherence. The findings reveal that the pesantren’s sustainability is constructed through the dynamic interaction of three interconnected dimensions: learning organization practices, optimization of local wisdom, and multi-dimensional sustainability (social, institutional, and economic). Local religious and cultural values function as a foundational resource internalized through shared vision, collective learning, and participatory leadership. These practices generate program innovations, including contextualized curricula, community engagement, and entrepreneurship-based economic empowerment. The resulting sustainability reinforces social legitimacy and strengthens institutional adaptability. This study proposes a dynamic and circular conceptual model of a local wisdom-based pesantren, demonstrating that sustainability is not a static outcome but an adaptive and self-reinforcing process. The findings contribute to Islamic educational management by positioning local wisdom as strategic cultural capital in building resilient and sustainable community-based educational institutions.